The role of debt capital in corporate financing: Overview of selected surveys - Katarzyna Czapińska (e-Finanse: Financial Internet Quarterly, 2013)
The ability to create a company's own capital structure with a simultaneous lack of universal solutions makes this issue a favorable subject of considerations. The aim of this article is to summarize selected surveys on the role of debt and financial leverage in corporate financing observed in the case of Polish companies. Based on the conclusions of the presented surveys, certain regularities were noticed. In most of the companies, equity was the main source of financing, whereas debt was used only in the case where internal sources of financing appeared to be insufficient. As a consequence of such an approach, the level of debt was relatively low and it may be concluded that companies benefited carefully from financial leverage. The external financing was limited to its most basic sources (i.e. bank loans and leasing). The conditions necessary to achieve the positive effect of financial leverage were most frequently met in large companies, which used external financing to a greater extent and had easier access to debt. The surveys confirmed that in principle a debt increase was not a consequence of detailed analysis of capital structure, but rather a result of current production needs or weak financial performance. It seems that tax shields (in a form of interest cost), increase of return on equity as a result of positive effects of financial leverage, target debt ratio as well as costs of financial distress generally did not significantly affect the decisions on sources of financing. On the contrary, risk of insolvency associated with financial leverage, credit rating, the availability of debt and its cost had a significant impact on the capital structure (with a major share of equity).
Keywords: G39; 330; debt; equity; capital structure; financial leverage